Inside Cover: Highly Stereoselective [4+2] and [3+2] Spiroannulations of 2‐(2‐Oxoindolin‐3‐ylidene)acetic Esters Catalyzed by Bifunctional Thioureas (Chem. Eur. J. 31/2015). Issue 31 (27th July 2015) - Monari, Magda; Montroni, Elisa; Nitti, Andrea; Lombardo, Marco; Trombini, Claudio; Quintavalla, Arianna
<x xml:space="preserve">Abstract</x> An efficient synthesis of β‐nitro spirocarbocyclic oxindoles containing multiple stereocenters has been developed mediated by thiourea‐based bifunctional organocatalysts, such as Takemoto's catalyst (TUC), as reported by A. Quintavalla et al. in their Full Paper on page 11038 ff. The catalyst promotes a cascade spiroannulation, starting from 3‐ylidene oxindoles and nitroenoates. A wide range of products is obtained in good yields and high stereocontrol. Depending on the nitro compound, both 5‐ and 6‐membered spirooxindoles are accessible. Furthermore, the nitroenoate double bond configuration determines the absolute configuration of the spiro center.